Secondary Varicocele Caused by Pancreatic Pseudocyst Obstructing Testicular Venous Drainage - Aswani, Yashant; Hira, Priya (JOP. Journal of the Pancreas, 2013)
A pseudocyst is a fluid/debris collection that occurs as a complication of pancreatitis. It can be symptomatic and cause compression of the surrounding structures. Our case report highlights a 29-year-old male who presented with secondary varicocele on left side caused by a huge pseudocyst seen to compress the left renal and testicular veins. Image: Prominence of testicular venous plexus (Videoclip).